2001
DOI: 10.1029/2000ja000344
|View full text |Cite
|
Sign up to set email alerts
|

Migrating thermospheric tides

Abstract: Abstract. The capabilities of the global-scale wave model (GSWM) [Hagan et al., 1995] are extended to include migrating thermospheric solar tides. The GSWM thermospheric tidal forcing parameterization is based on neutral gas heating calculated from first principles in the National Center for Atmospheric Research (NCAR) thermosphere/ionosphere electrodynamics general circulation model (TIE-GCM). This is the first time that a physics-based thermospheric forcing scheme has been used in a model like G SWM. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(172 citation statements)
references
References 42 publications
6
158
1
2
Order By: Relevance
“…It is clear that the change in solar activity may not have a direct significant effect on atmospheric tides in the ionospheric dynamo region (Bremer et al, 1997;Hagan et al, 2001), but the lunar tide amplitude intensification during solar maximum periods could be due to increased ionospheric conductivity. Ionospheric current intensity is dependent not only on the winds that drive the ionospheric dynamo but also on ionospheric conductivity, which depends on the intensity of the ionospheric electron density that is largely influenced by solar activity.…”
Section: Solar Cycle Variability In the Lunar Tidementioning
confidence: 99%
“…It is clear that the change in solar activity may not have a direct significant effect on atmospheric tides in the ionospheric dynamo region (Bremer et al, 1997;Hagan et al, 2001), but the lunar tide amplitude intensification during solar maximum periods could be due to increased ionospheric conductivity. Ionospheric current intensity is dependent not only on the winds that drive the ionospheric dynamo but also on ionospheric conductivity, which depends on the intensity of the ionospheric electron density that is largely influenced by solar activity.…”
Section: Solar Cycle Variability In the Lunar Tidementioning
confidence: 99%
“…6 and 7, respectively. For the purpose of comparison, the numerical model results from the Global Scale Wave Model 2000 (GSWM-00) (Hagan et al, 2001) and GSWM-02 (Hagan and Forbes, 2002) are also given in Figs. 6 and 7.…”
Section: Diurnal Tidementioning
confidence: 99%
“…gravity waves (GWs), tidal waves and planetary waves (PWs), which are believed to impact significantly on local and global atmospheric climatology (Alexander and Pfister, 1995;Alexander, 1998;Batista et al, 2004;Kishore et al, 2004). It is extensively accepted that these atmospheric waves are mainly excited in the lower atmosphere (Forbes and Leveroni, 1992;Smith, 1997;Hagan et al, 2001;Hagan and Forbes, 2002;Fritts and Alexander, 2003;Batista et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of observational and theoretical research in the recent decades, comprehensive understanding about the seasonal variability of tidal sources and background winds has been achieved (Hagan et al, 2001), and the primary seasonal variability of tides has been subsequently demonstrated. As the most widely accepted tidal models, the global-scale wave models (GSWMs) can provide the monthly averaged tides in the height range of 0-124 km and clearly display the latitude and season variability of tides.…”
mentioning
confidence: 99%